The economic impacts of telecommunications networks and broadband internet: A survey - Irene Bertschek; Wolfgang Briglauer; Kai Hüschelrath; Benedikt Kauf; Thomas Niebel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We provide a structured overview of the quantitative literature on the economic impacts of telecommunications networks and broadband internet. Differentiating between wireline and wireless technologies as well as broadband availability and broadband adoption, respectively, we review studies investigating the impacts on economic growth, employment and regional development as well as productivity and firm performance. Eventually, the survey does not only allow the identification of main research gaps but also provides useful information for policy makers on the significance and importance of communication networks for social welfare.
urn:nbn:de:bsz:180-madoc-414107
Keywords: D24; J23; J24; L96; O33; O47; 330; Telecommunications; Broadband; Economic Growth; Employment; Regional Development; Productivity